Elemen Fraud Hexagon dan Potensi Kecurangan Pelaporan Keuangan: Peran Ukuran Perusahaan sebagai Variabel Moderasi - Puan Sabrina Devi; Enny Susilowati Mardjono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the effect of Fraud Hexagon elements on the potential for fraudulent financial reporting and to investigate the moderating role of firm size in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. This research employs a quantitative approach with a causal research design. The sample consists of 152 firm-year observations selected using purposive sampling. Fraudulent financial reporting is measured using the Beneish M-Score, while hypothesis testing is conducted through multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that external pressure and ineffective monitoring have a positive and significant effect on the potential for fraudulent financial reporting. Conversely, change in auditor, change in director, and arrogance do not significantly affect the potential for fraudulent financial reporting. Collusion is found to have a significant negative effect on fraudulent financial reporting. Furthermore, firm size moderates the relationship between external pressure, arrogance, and collusion and the potential for fraudulent financial reporting, but does not moderate the effects of ineffective monitoring, change in auditor, and change in director. The findings highlight external pressure and ineffective monitoring as the primary factors that increase the risk of fraudulent financial reporting, while firm size influences the strength of several Fraud Hexagon relationships. This study contributes to the development of fraud detection literature and provides practical implications for strengthening corporate governance and fraud prevention efforts.